Assessing the Impact of Exposure to PM2.5 Air Pollution on the Academic Performance of Schoolchildren in Chile - Andrea González-Rojas; Hanns de la Fuente-Mella; Sonnia Parra; Fernando Cancino-Haas; Catalina Coiro-Nicolas; Javiera Godoy-Saavedra; Melanie Pastén-Torres; Elizabeth Verdejo-Zamora; Agustín Dotte-González; Paulo Salinas; Martina Valencia-Narbona; Oscar Achiardi; et al. (Applied Sciences)
Air pollution from particulate matter 2.5 (PM2.5) may negatively impact students’ learning due to its neurotoxic effects. Therefore, we ask: What is the effect of PM2.5 air pollution on the academic performance of Chilean eighth-grade students? Objective: To compare the academic performance of eighth-grade students living in the three most PM2.5-polluted areas of Chile with those living in the three least polluted areas. Additionally, we compared the academic performance of schools in the most and least polluted areas according to their administrative dependency. Methodology: Academic performance was assessed using the results of the 2019 SIMCE test (mathematics, and language score). The most and least polluted areas were determined based on the three-year average PM2.5 levels reported by the Chilean Ministry of the Environment. Results: The mathematics and language scores were lower in schools located in areas with higher pollution PM2.5 with a small effect size. When analyzing the scores by administrative dependency, students from subsidized schools in highly polluted areas obtained lower scores in all tests compared to those in less polluted areas, a pattern not observed in private or municipal schools. Conclusion: These findings suggest that PM2.5 pollution alone may not fully explain variations in academic performance, highlighting the need to explore additional contributing factors.